Administration of estates in Malaysia: Determinant of factors behind the delay in the distribution of the deceased’s asset - Drs Nasrul, Muhammad Amrullah; Mohd Salim, Wan Noraini (Penerbit Universiti Sultan Zainal Abidin, 2018)
The distribution of the deceased’s estate depends on the smooth process of estate administration. Apart from the personal representative, the beneficiaries hold a significant role in the administration, not as recipients of the deceased’s estate but as participants in the estate administration process. Despite the clear laws governing the succession matters in Malaysia, issues of delay in distribution of estate continue to occur, being the result of unresolved disputes between the beneficiaries. As a result, there are over sixty billion ringgit worth of unclaimed estate in Malaysia as reported by various sources, indicating the seriousness of the matter. This paper addresses the problems of delay in the administration of the estates and analyzes its causes and implications. The lack of knowledge and the attitude of the beneficiaries has been identified as the key factors which lead to such problem. This paper is based primarily on the analysis of written sources namely conference papers, textbooks, statutes, case laws, journals and other library-based documents. The findings in this article show that there is a need for a cohesive approach to educate the beneficiaries of the law and to change their attitude in understanding their actual roles in the deceased’s estate administration.